Reduced mortality with partial-breast irradiation for early breast cancer: a meta-analysis of randomized trials - Vaidya, Jayant S.; Wenz, Frederik (International journal of radiation oncology, biology, physics, 2016)
Purpose - With earlier detection and more effective treatment, mortality from breast cancer continues to fall and it has become increasingly important to reduce the toxicity of treatments. Partial-breast radiation therapy, which focuses radiation to the tumor bed, may achieve this aim. We analyzed mortality differences in randomized trials of partial-breast irradiation (PBI). - Methods and Materials - We included data from published randomized trials of PBI (alone or as part of a risk-adapted approach) versus whole-breast irradiation (WBI) for invasive breast cancer suitable for breast-conserving therapy. We identified trials using PubMed and Google searches with the terms “partial breast irradiation” OR “intraoperative radiotherapy” OR “IMRT” OR (“accelerated” AND “radiation”) AND “randomised/randomized,” as well as through discussion with colleagues in the field. We calculated the proportion of patients who had events in each randomized arm at 5 years' follow-up and created a forest plot using Stata, version 14.1. - Results - We identified 9 randomized trials of PBI versus WBI in invasive breast cancer; 5-year outcomes were available for non-breast cancer mortality in 5 trials (n=4489) and for breast cancer mortality in 4 trials (n=4231). The overall mortality was 4.9%. There was no detectable heterogeneity between the trials for any of the outcomes. There was no difference in the proportion of patients dying of breast cancer (difference, 0.000% [95% confidence interval (CI), −0.7 to +0.7]; P=.999). Non-breast cancer mortality with PBI was lower than with WBI (difference, 1.1% [95% CI, −2.1% to −0.2%]; P=.023). Total mortality with PBI was also lower than with WBI (difference, 1.3% [95% CI, −2.5% to 0.0%]; P=.05). - Conclusions - Use of PBI instead of WBI in selected patients results in a lower 5-year non-breast cancer and overall mortality, amounting to a 25% reduction in relative terms. This information should be included when breast-conserving therapy is proposed to a patient.